2010
DOI: 10.1530/eje-10-0570
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and placebo therapy both improve weight management and fasting insulin in obese insulin-resistant adolescents: a prospective, placebo-controlled, randomized study

Abstract: Objective: To study whether metformin reduces obesity, homeostasis model assessment for insulin resistance index (HOMA-IR), and the metabolic syndrome (MtS) in obese European adolescents in addition to previous unsuccessful lifestyle intervention. Design and methods: After 6 months of multiprofessional lifestyle intervention, 70 out of 86 adolescents without improvement in body mass index (BMI) and HOMA-IR were randomized into either the placebo (nZ34) or the metformin group (2!500 mg/day, nZ36) in addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 29 publications
3
83
1
4
Order By: Relevance
“…PCOS women randomized to both metformin and lifestyle interventions (compared to placebo) showed improvements in HOMA IR after 4 mo [106] . In European adolescents with PCOS who failed to achieve improvements in HOMAIR after 6 mo of lifestyle intervention, both metformin and placebo reduced IR over 6 mo, although metformin offered no benefit over placebo [107] . Lifestyle modification in ado lescents has been successful in reducing hyperandroge nism [103] .…”
Section: Treatmentmentioning
confidence: 94%
“…PCOS women randomized to both metformin and lifestyle interventions (compared to placebo) showed improvements in HOMA IR after 4 mo [106] . In European adolescents with PCOS who failed to achieve improvements in HOMAIR after 6 mo of lifestyle intervention, both metformin and placebo reduced IR over 6 mo, although metformin offered no benefit over placebo [107] . Lifestyle modification in ado lescents has been successful in reducing hyperandroge nism [103] .…”
Section: Treatmentmentioning
confidence: 94%
“…Fourteen trials were identified [15,16,17,18,19,20,21,22,23,24,25,26,27,28]. However, 3 studies [16,20,23] were excluded for their short duration (<6 months).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, 11 trials were selected for inclusion in this review. All the trials included are double-blind randomized placebo-controlled studies [15,17,18,19,22,24,25,28], except 3 [21,26,27] which are not placebo controlled. In those studies, the metformin group (metformin plus lifestyle intervention) was compared with a lifestyle intervention alone group (placebo was not administered).…”
Section: Methodsmentioning
confidence: 99%
“…Recent intervention studies have convincingly demonstrated that adoption of a healthy lifestyle characterized by healthy eating, regular physical activity and subsequent modest weight loss can prevent the progression of impaired glucose tolerance to clinical diabetes mellitus [76] . However, the use metformin was not effective to prevent type 2 diabetes mellitus in obese adolescents with impaired glucose tolerance [77] . This might be attributed to the fact, that impaired glucose tolerance normalized physiologically at the end of puberty even without intervention [20] .…”
Section: Prevention Of Type 2 Diabetes Mel-litus In Children and Adolmentioning
confidence: 96%